1-MW solar power inverter with boost converter using all SiC power module. Issue 4 (1st October 2016) - Fujii, K.; Noto, Y.; Okuma, Y.
Abstract: Recently, the market of the PV power plant is growing up in the Asian market. In the PV power plant, typically, an inverter which has the rated power of few hundreds kVA is applied to feed the power to the grid. A 1-MW solar power inverter which employs all SiC Power Modules has been developed. The developed solar power inverter consists of two conversion stages, first stage is a boost converter and second stage is a T-type NPC inverter. A chopper module in the boost converter is configured with SiC-based MOSFETs and Schottky Barrier Diodes, and 48 chopper modules are used in parallel. Each chopper module is controlled individually. The T-type NPC inverter stage is configured with Si-based IGBTs and RB-IGBTs. In this paper, the circuit configurations of the developed solar power inverter, employed SiC-based power devices, and the control scheme are described in detail. In the end, the total efficiencies for the minimum, nominal, and maximum DC voltages are experimentally measured. The measured efficiency at the rated output power varies from 98 to 98.6% depending on the values of DC input voltage. The maximum efficiency of 98.8% is achieved in the case of maximum DC input voltage.